Genetic characterization of Kedah Kelantan cattle and its crossbred types in Malaysia - Abdelwahid Bashir, Haytham Hago (2012)
The Kedah Kelantan (KK) is the indigenous cattle breed of Malaysia and is mainly kept by small farmers for meat production because of its small and compact body, and low maintenance requirement. This breed faces risk of germplasm dilution due to extensive crossbreeding and breeds replacement practices in the country. The population size of purebred KK is fast decreasing and most of the commercial populations are actually crossbreds. There is a lack of information on the genetic characteristics of KK. The genetic relationships between the KK, the synthetic breeds developed using the KK as the maternal line, as well as the nondescriptive KK crossbred types are also unknown. It is with these in mind that the present study was conducted. The objective of the study was to evaluate the genetic variability within and among the indigenous KK cattle and the KK crossbred types in Malaysia. DNA was extracted from the blood of 312 randomly selected animals of six cattle breed types. These included the Kedah Kelantan (KK), the Brakmas and Charoke which are synthetic breeds developed through crossbreeding of the KK, two non descriptive KK crosses (KKX1 & KKX2), and the Brahman (used as an outgroup). The breed types were assessed for 30 microsatellite loci recommended by FAO/ISAG for cattle genetic diversity studies. PCR was accomplished by using a touchdown programme. The PCR products were separated using capillary electrophoresis. Prior to screening the breed types, three genotyping methods were evaluated by comparison to the sequence information for two microsatellite loci, ETH152 and INRA005. Twelve DNA samples from KK were used for this purpose. The result indicated that the capillary electrophoresis system using labelled primers provided higher genotyping accuracy in microsatellite analysis compared to capillary electrophoresis system requiring no primer labelling primers or electrophoresis using MetaPhor agarose gel. Therefore, this method was chosen for fragment analysis in the present study. The results showed that all 30 microsatellites loci were polymorphic for all the breed types, with 8 to 18 alleles per locus. Heterozygosity values observed for all breed types were moderate and ranged from 0.54 (KK) to 0.65 (Charoke), and were lower than the expected heterozygosity values. Seven loci (BM1818, ETH3, HEL5, HEL9, ILSTS005, INRA063 and TGLA53) showed significant (P < 0.05) deviation from Hardy-Weinberg Equilibrium (HWE) for all the breed types. No breed type was observed to deviate from HWE for all 30 loci. The mean of inbreeding coefficient (FIS) ranged from 0.149 (Charoke) to 0.232 (KKX2); this indicated inbreeding was present in all breed types and could lead to loss of genetic diversity if not addressed. No recent bottleneck effect was detected in any of the breed types. The genetic distance between KK and the two KK crosses (KKX1 and KKX2) was lower than those between KK and the two synthetic breeds. Brakmas and Charoke tended to be the most distantly related. In general, the genetic differentiation measures were moderate, with a mean FST of 0.054. The analysis of molecular variance (AMOVA) indicated a greater proportion of the genetic diversity was within the breed types (96.6%) than between them. The structure analysis, phylogenetic trees, and principal component analysis showed that the breed types could be grouped into three clusters: KK and KKX2 in the first cluster, Brakmas and Brahman in second, and Charoke and KKX1 in third cluster. Structure analysis also showed that a few of the Brakmas and Cheroke animals were more KK in their genetic background;and so were many animals from the two non descriptive KK cross breed types. Analysis of zebu and taurine diagnostic alleles showed that all breed types had low proportion of African taurine and European taurine diagnostic allele. It may be concluded that there is still some genetic variation present in the KK and KK crossbred types. However, this genetic diversity is at risk of being lost if no appropriate breeding practices are implemented. The Charoke and Brakmas may be considered as genetically distinct breeds.